Carotid artery longitudinal wall motion alterations associated with metabolic syndrome and insulin resistance - Taivainen S Helena; Laitinen Tiina M; Yli-Ollila Heikki; Juonala Markus; Kähönen Mika; Raitakari Olli T; Laitinen Tomi P (WILEY, 2025)
Background and aims: Our objective was to study relationships between the new biomarker of vascular health, carotid artery longitudinal wall motion (CALM) and metabolic syndrome (MetS).
Methods: Carotid ultrasound and assessment of MetS and its components were performed with 281 subjects aged 30-45 years. In the longitudinal motion analysis, the amplitude of motion and the antegrade-oriented and retrograde-oriented components of motion between the intima-media complex and adventitial layer of the common carotid artery wall were assessed.
Results: Metabolic syndrome, according to the harmonized criteria, was detected in 53 subjects (19%). MetS was significantly associated with increased antegrade and decreased retrograde longitudinal motion in the carotid artery wall. Augmented antegrade amplitude of longitudinal motion was associated with obesity (β = 0.149, p < .05) and low HDL cholesterol (β = 0.177, p < .01). Attenuated retrograde amplitude of longitudinal motion was associated with hypertension (β = -0.156, p < .05), obesity (β = -0.138, p < .05) and hyperinsulinaemia (β = -0.158, p < .01). Moreover, insulin resistance (homeostasis model assessment index above 2.44) was associated with adverse changes in CALM.
Conclusion: Metabolic syndrome and insulin resistance were associated with alterations in CALM. In particular, hypertension, obesity and hyperinsulinaemia were associated with reduced total peak-to-peak amplitude as well as increased antegrade and reduced retrograde amplitudes, all of which might be markers of unfavourable vascular health.